Axiological Study of Christian Teachers As Role Model in Providing Motivation for Students - Advenita, Vannesa El Shaday Ruth; Bermuli, Jessica Elfani (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Extrinsic motivation is an important factor in learning. However, many teachers have not been able to provide proper motivation by giving negative labeling to students. This happens because the teacher does not yet have the proper axiological foundation in viewing students as the image and likeness of God. Therefore, the aim of this study is to analyze the axiological study of the teacher's role as a role model in providing motivation for students. The method used is a literature study. The result of the study showed that the Christian teacher needs to live up to the values in the Bible so that the teacher has the basic values of correct behaviour, namely the Word of God. Teachers must also imitate Christ because He is the perfect role model for humans.